The Integration of the Visegrad Group Countries with the EU in the Conditions of Globalisation - Puáleck, Zdzislaw W. (2001)
The suggested research subject conceming inclusion of the Visegrad Group Countries in the processes ofintegration within the European Union in the condi tion of globalisation of contemporary world economy is topical and important from a theoretical and practical point of view. A gradual integration ofthe Viseg rad Group Countries with the European Union has provided opportunities for a faster development ofthis region. Both the processes ofpoliticalsystemic transfor mation in this part ofEurope and diverse types of aids provided by the European Union in the 1990s have contributed to decreasing developmental differences between the East and West ofEurope. A significant challenge to the Visegrad Group Countries was stimulation ofeconomic policies and institutional changes so as to achieve macroeconomic stabilisation and to trigger the formation of structures facilitating economic development.